Kuching District Education Office / Mohd Izham Ahmar Saberi - Ahmar Saberi, Mohd Izham (University Technology MARA Sarawak, 2017)
Kuching District Education Office (PPDK) is a part of Sarawak Education Department (JPNS). There are 26 high schools and 61 primary schools under the administration of Kuching District Education Office. Meanwhile, Kuching District Education Office was operating according to the procedure and the decision of Sarawak Education Department (JPNS) because it was under part ofSarawak Education Department (JPNS).